Comprehensive transformation in unused degrading landscaped urban areas’ development - Leshchenko, Nellya; Holovatiuk, Alina (Landscape Architecture and Art, 2024)
According to the defined aim of the article, the methodology for the comprehensive transformation of unused degrading landscaped urban areas is proposed, based on the determination of a qualitative indicator of their existing state – the degrees of their historical and architectural value and destruction. The corresponding possible restorative (preserving and restoring) and reconstructive (renewing and transforming) methods of transformation depending on the degrees of value and destruction of a certain area are determined. The most effective combinations of various restorative and reconstructive methods for the realization of comprehensive transformation at different system levels – urban planning, volumetric, and functional, for unused degrading landscaped urban areas, depending on combinations of initial degrees of their historical and architectural value and destruction, are proposed. The principles of the comprehensive transformation of degrading landscaped urban areas, such as “cumulative development”; “contextual complementation”; “attractive spatial disclosure” and “multi-comfort” are formulated. Combinations of planning, volumetric-spatial, and functional transformation of urban space techniques are identified, which reveal the proposed principles, reinforcing each other’s action, and make it possible to effectively recover and improve the quality of abandoned urban space, make it active and attractive for people with different preferences and capabilities. Approbation of the put-forward theoretical provisions in the concept of transformation and development of the degrading area along Pogulyanka Street in L’viv was carried out, which confirmed the effectiveness of the proposed methodology.